ONLINESHOP SEBAGAI CARA BELANJA DI KALANGAN MAHASISWA FISIP UNIVERSITAS RIAU - Gunawan, Randy; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This thesis was submitted to meet the requirements for a bachelor's degree in sociology with the title